Desenvolvimento de fósforos cerâmicos nanoestruturados puros e dopados com terras raras - Tavares, Fabio dos Santos [UNIFESP] (2017)
Molybdates, with the general formula AMoO4 (A = Ca, Sr, Ba) and crystalline structure scheelite, have optical properties that make them potential candidates for use in optical devices. In the present work, calcium molybdate (CaMoO4) was doped with three rare earth ions: cerium, terbium and europium. Five types of doped materials were synthesized via Complex Polymerization Method (MPC) in addition to CaMoO4, which were divided into: three types of molybdates doped with 1% TR in relation to the Ca2+ ion Ca0,99Eu0,01MoO4, Ca0,99Tb0,01MoO4 and Ca0,99Ce0,01MoO4: Ca 0.99Eu 0.01MoO 4, CaO, 99Tb0.01MoO4 and Ca0.99Ce0.01MoO4, and two types of calcium molybdates co-doped with Ce, Tb, Eu: Ca0,97Eu0,01Tb0,01Ce0,01MoO4 and Ca0,991Eu0,0033Tb0,0033Ce0,0033MoO4. The ceramic powders obtained were characterized by XRD, Raman, MEV, Photoluminescence, FTIR, Diffuse Reflectance and XPS. With the variation of the thermal treatment temperature (400-900 ° C), we observed the modification of the properties of the doped materials when compared to the CaMoO4. Among them, there was an increase in the organization of materials with increasing temperature. With a better organization of the materials, we obtained more homogeneous and rounded grains and an amplification of the luminescent properties, obtaining emissions in the green-yellow region, of the red and low emission in the blue. The co-doped molybdates presented variations in the color of the resulting emission dependent on the heat treatment temperature applied, ranging from orange to red. X-ray diffraction allowed us to identify the Scheelite structure in pure and doped molybdates. The lanthanide ions effectively replaced the modifier ion of the network (Ca2+). Through the characterization, we observed short and long range order in the studied materials. Typical modes of asymmetric stretch and stretch stretching were detected through FTIR. Diffuse reflectance spectroscopy was used mainly for the band gap calculation. The results of this work indicate that the photoluminescent emission characteristics of the doped and co-doped calcium molybdates are of interest for application in optical devices.